2021
DOI: 10.1158/2159-8290.cd-20-0318
|View full text |Cite
|
Sign up to set email alerts
|

The Hepatic Microenvironment Uniquely Protects Leukemia Cells through Induction of Growth and Survival Pathways Mediated by LIPG

Abstract: Due to the disseminated nature of leukemia, malignant cells are exposed to many different tissue microenvironments, including a variety of extramedullary sites. In the present study, we demonstrate that leukemic cells residing in the liver display unique biological properties, and also contribute to systemic changes that influence physiological responses to chemotherapy. Specifically, the liver microenvironment induces metabolic adaptations via up-regulating expression of endothelial lipase (LIPG) in leukemia … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Observations made here may also help explain why several systemic oxidant stressors that regularly occur during ongoing physiological changes from exercise 5 to aging 8 and in progressive pathophysiological process from neurological disease 13 to cancer 14,15 are all associated with increases in the degree of unsaturation of RBC lipids. This consideration warrants attention in that it would suggest that findings relevant to RBC biology could also contribute to advancing knowledge of cancer biology, where FADS are being increasingly tied to metabolic reprogramming, a driver of malignant transformation 28,53,54 . Side‐by‐side understanding of these processes could uniquely advance blood storage and cancer treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Observations made here may also help explain why several systemic oxidant stressors that regularly occur during ongoing physiological changes from exercise 5 to aging 8 and in progressive pathophysiological process from neurological disease 13 to cancer 14,15 are all associated with increases in the degree of unsaturation of RBC lipids. This consideration warrants attention in that it would suggest that findings relevant to RBC biology could also contribute to advancing knowledge of cancer biology, where FADS are being increasingly tied to metabolic reprogramming, a driver of malignant transformation 28,53,54 . Side‐by‐side understanding of these processes could uniquely advance blood storage and cancer treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with quizartinib showed an immediate effect on the metabolism of AML cells (Gregory et al, 2016(Gregory et al, , 2018Gallipoli et al, 2018) and we confirm that this also applies to gilteritinib (Table S3). FGF2 or FL did not restore the pre-treatment metabolic phenotype, but rather revealed distinct adaptations, indicating the influence of the microenvironment on metabolism (Ye et al, 2020;Savino et al, 2020;Van Gastel et al, 2020;Forte et al, 2020) (Figure 4). FGF2 late cultures displayed altered sphingolipid metabolism, whereas FL late cultures preferentially utilized carnitine/fatty acid metabolism (Figures 4D-4I).…”
Section: Discussionmentioning
confidence: 99%
“…111 In the same murine model, LSC in the liver, a common extramedullary site for leukemic infiltration, showed increased pathways for lipid metabolism in the absence of an inflammatory profile. 112 The metabolome of cells isolated from the liver and BM showed abundant polyunsaturated fatty acids in the hepatic lin − leukemic cells. Significantly, culturing LSC with polyunsaturated fatty acids increased the number of LSC, with linoleic acid being the most mitogenic fatty acid.…”
Section: Lsc In Amlmentioning
confidence: 99%